Evaluation of Bovine chemerin (RARRES2) Gene Variation on Beef Cattle Production Traits1 - Lindholm-Perry, Amanda K.; Kuehn, Larry A.; Rempel, Lea A.; Smith, Timothy P.; Cushman, Robert A.; McDaneld, Tara G.; Wheeler, Tommy L.; Shackelford, Steven D.; King, David A.; Freetly, Harvey C. (Frontiers in Genetics, 2012)
A previous study in cattle based on >48,000 markers identified markers on chromosome 4 near the chemerin gene associated with average daily feed intake (ADFI) in steers (P<0.008). Chemerin is an adipokine associated with obesity and metabolic syndrome in humans, representing a strong candidate gene potentially underlying the observed association. To evaluate whether the bovine chemerin gene is involved in feed intake, 16 markers within and around the gene were tested for association in the same resource population. Eleven were nominally significant for ADFI (P<0.05) and two were significant after Bonferroni correction. Two and five SNP in this region were nominally significant for the related traits of average daily gain (ADG) and residual feed intake (RFI), respectively. All markers were evaluated for effects on meat quality and carcass phenotypes. Many of the markers associated with ADFI were associated with hot carcass weight (HCW), adjusted fat thickness (AFT), and marbling (P<0.05). Marker alleles that were associated with lower ADFI were also associated with lower HCW, AFT, and marbling. Markers associated with ADFI were genotyped in a validation population of steers representing 14 breeds to determine predictive merit across populations. No consistent relationships for ADFI were detected. To determine whether cattle feed intake or growth phenotypes might be related to chemerin transcript abundance, the expression of chemerin was evaluated in adipose of 114 heifers that were siblings of the steers in the discovery population. Relative chemerin transcript abundance was not correlated with ADFI, ADG, or RFI, but associations with body condition score and yearling weight were observed. We conclude that variation in the chemerin gene may underlie observed association in the resource population, but that additional research is required to determine if this variation is widespread among breeds and to develop robust markers with predictive merit across breeds.